The Impact of Artificial Intelligence on Thesis Writing Skills and Quality among Students at UPN "Veteran" Yogyakarta - Kusumo, Yudhy Widya; Simanjuntak, Oliver Samuel; Wiendijarti, Ida; Utami, Yenni Sri (Jurnal Ilmu Komunikasi, 2024)
This study examines the influence of artificial intelligence (AI) on students' thesis-writing abilities in higher education by evaluating its effects on writing proficiency, draft quality, and efficiency in thesis completion. The research employs Partial Least Squares (PLS) structural equation modeling to analyze data collected from 120 undergraduate students at UPN "Veteran" Yogyakarta who frequently utilized AI tools such as Turnitin and Grammarly. Structured questionnaires with high reliability and validity were used for data collection. The findings reveal that AI tools significantly enhance technical aspects of thesis writing, including grammar, coherence, and vocabulary, resulting in improved thesis quality. However, their contribution to developing deeper academic skills, such as critical thinking and argumentation, remains limited. While AI tools effectively address surface-level issues and provide valuable suggestions, they do not adequately support the cultivation of advanced intellectual abilities required for rigorous academic writing. This study highlights the importance of integrating AI tools with traditional teaching methods. Educators are encouraged to use AI to assist with technical writing while continuing to teach critical thinking and argumentation to develop well-rounded writing skills. A balanced approach combining AI technology and human guidance is essential for fostering both technical proficiency and the intellectual depth necessary for high-quality thesis writing.